Kontribusi Mahasiswa PKKB Proyek Desa dalam Meningkatkan Mutu Pendidikan melalui Program Pembinaan dan Pelatihan Olahraga Prestasi di Desa Semoyang - Muh. Taufik Adnan; Lalu Ubaidi; Gaibul Gunawan; Mardian Cahyo Suwendi; Hardianto Saputra; Karno Dinata (Pusat Riset dan Inovasi Nasional, 2024)
This community service article discusses the contribution of students from the Impactful Campus Competition Program (PKKB) in improving the quality of education through coaching and training activities in sports in Semoyang Village, Praya Timur Subdistrict, Central Lombok Regency. This activity was carried out using a participatory action research method involving three main stages, namely planning, preparation, and implementation. In the planning stage, students and the community worked together to identify the needs and objectives of activities relevant to local potential. The preparation stage focused on developing training strategies, providing facilities, and coordinating with relevant parties. The implementation stage was carried out through sports coaching activities for children and adolescents using an educational and participatory approach. The results of the activity showed an increase in community awareness of the importance of sports from an early age, as well as a growing concern for environmental cleanliness and health. This program also played a role in strengthening social interaction, building a spirit of togetherness, and fostering community independence in managing sports activities. Overall, the PKKB activities in Semoyang Village have succeeded in creating positive synergy between universities and the community in supporting the development of healthy, competitive, and characterful human resources.